Introducing the precisionflex grinder: a revolutionary adjustable cutting solution - Zulkarnain, Mohamad Fauzan Akmal; Mohd Yusof, Ab Aziz; Abu Kasim, Haszeme (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study develops the PrecisionFlex Grinder as an innovative solution to meet the modern manufacturing demand for adaptable cutting tools by overcoming traditional grinders' limitations. Traditional cutting tools struggle with varying material thicknesses, hardness levels, and cutting angles, resulting in operational inefficiencies and higher costs because of the need for multiple specialized tools. The research tackled these problems using a systematic process that combined design conceptualisation with SolidWorks simulation and iterative testing to achieve performance optimisation. Stress tests on the grinder holder confirmed material suitability, as the maximum stress remained below the yield strength limit. Performance tests revealed traditional tools were outperformed as cutting times dropped by up to 50% across aluminum and mild steel sheets of different thicknesses. The PrecisionFlex Grinder demonstrates enhanced workflow efficiency while minimising costs and improving precision and adaptability. The next development phase will incorporate intelligent systems while minimizing noise and vibration levels and testing new eco-friendly materials to boost performance attributes. The study demonstrates that merging theoretical design principles with practical manufacturing techniques leads to the development of advanced tools that address industries' changing requirements.